The Skills of the Students and the Teachers in the 21st Century According to the International Discourse - Polydorou, Vasiliki; Karanikola, Zoe; Panagiotopoulos, George (International Journal of Learning and Development, 2024)
Following the guidelines of the Agenda 2020, the international Organisations and the European Union have laid the foundations of educational policy. Every person’s right to quality education is put forward to every international document, considering education as the means for the prosperity of all the people and the planet. Through qualitative analysis, with the use of thematic networks, three documents: of UNESCO, (2017) “E2030 education and skills for the 21st century”, of the OECD, (2019) “future of Education and skills 2030: OECD learning compass 2030” and of the European Commission, (2018). “Annex of the Recommendation for the establishment of a Council regarding the basic skills of lifelong learning”, the modern skills required of students as well as teachers are explored, since their acquisition is imperative, as well as the manner of this acquisition are being examined. Thus arose the necessity of acquiring digital and social skills, lifelong learning culture, citizenship and ecology learning. Additionally, the necessity of modification of education is put forward. Finally, it is important that educators receive proper education, so that they acquire new knowledge, attitudes, skills to be able to respond to their role as vehicles of change.